Report of the Fourteenth Finance Commission Volume I - Ministry of Finance (Department of Economic Affairs, Ministry of Finance, Government of India)
The Fourteenth Finance Commission (FC-XIV), constituted under Article 280 of the Constitution in January 2013 with Dr. Y. V. Reddy as Chairman, was mandated to make recommendations for the period 2015–20. Its Terms of Reference required assessment of the distribution of tax proceeds between the Union and States, principles for grants-in-aid to States, augmentation of State resources for Panchayati Raj institutions and Municipalities, and measures for fiscal consolidation consistent with equitable growth. The Commission was also tasked with reviewing public expenditure management, disaster management financing, and the implications of reforms such as the Goods and Services Tax. Additional responsibilities included consideration of resources of reorganized States following the bifurcation of Andhra Pradesh. The Commission faced initial administrative challenges, including office space, staffing, and data collection, which were addressed through temporary arrangements and deputation-based recruitment. Extensive consultations were held with State Governments, Union Ministries, experts from diverse disciplines, regional workshops, Accountants General, and previous Finance Commissions to gather comprehensive inputs. The Commission also conducted interactions with the public, economists, policy makers, and academic institutions to inform its recommendations. These structured procedures ensured robust data collection, validation, and analysis, providing a foundation for evidence-based recommendations on equitable fiscal devolution, sustainable public finances, and effective governance for both the Union and State Governments.
Department of Economic Affairs, Ministry of Finance, Government of India
Keywords: Fourteenth Finance Commission, Terms of Reference, Union Government, State Governments, Grants-in-Aid, Fiscal Consolidation, Public Finances, Andhra Pradesh Reorganisation, Administrative Arrangements, Data Collection, Regional Workshops, Consultations